Performance Of Domestic Airlines In Kenya: The Role Of Strategic Management Practices - Georgina Shiboko Ichingwa; Sarah Kamau (Equivalent : Journal of Economic, Accounting and Management, 2025)
The study sought to examine the effect of strategic management practices on performance of domestic airlines in Kenya. This comes at a time when the domestic airlines in Kenya have been facing tremendous challenges orchestrated by dynamics in the operating environment and disruptions in the global markets. The domestic airlines have seen a surge in customer-shun rate due to low customer satisfaction. Moreover, most of the players in domestic airlines have faced a steady decline in sales revenues and the overall market share. This raises the question on what could be the remedy to upscale organizational performance of domestic airlines. The study specifically addressed the effect of environmental scanning, strategy formulation, strategy implementation and strategy evaluation on performance of domestic airlines in Kenya. The study employed a descriptive survey approach, and targeted 129 employees drawn from 43 domestic Kenyan airlines. A questionnaire was used to collected primary data for the study, which was analysed using descriptive and inferential statistics. The findings revealed that strategic management practices (environmental scanning, strategy formulation, strategy implementation and strategy evaluation) significantly influenced performance of domestic airlines in Kenya.  It was therefore concluded that the deficiencies in performance of domestic airlines in Kenya was strongly associated with effective embrace of strategic management practices. It is recommended that for the domestic airlines to expand and continue performing in the current competitive market, the managers have a duty to integrate strategic management practices through vigorous environmental scanning, formulation of strategies that respond to market demands, effective implementation of developed strategies and evaluation of implemented strategies to ensure they align with the external operating market for enhanced performance.